Uso de sistemas de medição de desempenho para melhoria contínua: um estudo da influência do estilo de gestão - Goessler, Luiz Geraldo Micheletti (Universidade Federal de São Carlos, 2009)
Performance measurement systems are part of the daily routine of managers, due to the fact that organizations under their administration operate in a dynamic, complex environment where information-based decision and action taking are vital. Several uses to performance measurement systems can foster improvements. To any of these purposes the performance measurement systems are always driving behavior to process improvement. In doing so, they can act as an enabler to continuous improvement programs since other organizational factors allow this use. In performance measurement systems literature no factor is so commented as organizational culture however. In this research field, this factor is commonly handled as managerial behavior, or managerial style, used by managers in charge of the managerial control. The aim of this dissertation is to clarify the relationship between managerial style and the use of performance measurement systems as an enabler of continuous improvement initiatives. An exploratory study was developed using participant observation and document review techniques in case studies. Empirical results show that the use of performance measurement systems in an interactive way is achieved through a process-relational management style. In this case there is more commitment to continuous improvement programs. On the other hand, the use of performance measurement systems in diagnostic way is achieved through a systemic-control management style. In this case there is less commitment to the continuous improvement programs. Furthermore, the use of performance measurement systems as an enabler of continuous improvement programs depends on its use as an interactive control system in al management levels and in the whole measurement cycle.
Keywords: Sistemas de medição de desempenho; Melhoria contínua; Medição de desempenho; Gestão da qualidade; Estilo de gestão; Performance measurement systems; Continuous improvement; Managerial style; ENGENHARIAS::ENGENHARIA DE PRODUCAO